Blackburn. The Overthrow of Colonial Slavery, 1776-1848 - Shrock, Randall (Teaching History: A Journal of Methods, 1991)
Robin Blackburn's work is an extraordinary study of anti-slavery throughout the Western hemisphere. It offers a sweeping investigation of the complex origins of anti-slavery, giving attention not only to abolitionists but also to political crises in imperialist powers, to slave resistance and rebellion, and to social and political pressures that impelled "metropolitan decision makers" to accept anti-slavery.